2016
DOI: 10.5539/ep.v5n1p60
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Pyrethroids Pesticide Residues in Soils and Drinking Water Sources from Cocoa Farms in Ghana

Abstract: The contamination of pesticides in 32 soils and 64 drinking water samples was investigated from cocoa farms in the Dormaa West District of Ghana to assess pollution status. A total of nine synthetic pyrethroids pesticides were measured with a high resolution Varian CP-3800 Gas Chromatograph equipped with 63 Ni electron capture detector (ECD). Eight synthetic pyrethroid residues namely fenvalerate, deltamethrin, cypermethrin, bifenthrin, permethrin, lambda-cyhalothrin, allethrin and cyfluthrin were detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 31 publications
0
9
1
Order By: Relevance
“…Previous studies in Ghana have found insecticide contamination in soil, drinking water, surface water, fishes, and mosquito-breeding habitats ( Achonduh et al 2008 , Essumang 2015 , Gbeddy et al 2015 , Fosu-Mensah et al 2016 ). However all of them were associated with agricultural activities or large water bodies that receive runoff from several sources including agricultural areas.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies in Ghana have found insecticide contamination in soil, drinking water, surface water, fishes, and mosquito-breeding habitats ( Achonduh et al 2008 , Essumang 2015 , Gbeddy et al 2015 , Fosu-Mensah et al 2016 ). However all of them were associated with agricultural activities or large water bodies that receive runoff from several sources including agricultural areas.…”
Section: Discussionmentioning
confidence: 97%
“…So far, there has been only one study exploring the presence of pyrethroids in the soil of tea plantation, e.g., in India [18], but unfortunately, none of synthetic pyrethroids were detected in the soils of that region, therefore, pyrethroid levels detected in the present study were compared with those in other studies that successfully detected pyrethroid residues in soils from various tropical ecosystems. In previous studies conducted in different types of tropical plantation [13,[15][16][17], deltamethrin was detected in cotton/wheat soil (6 × 10 − 5 − 1.8 μg g − 1 ), chestnut soil (< LoD -0.03 μg g − 1 ), walnut soil (< LoD -0.02 μg g − 1 ), pinenut soil (< LoD -0.005 μg g − 1 ), cabbage soil (0.007-0.008 μg g − 1 ), and cacao soil (0.04 μg g − 1 ). Meanwhile, permethrin has never been detected in plantation soils but it was detected in rivers near the plantation (< 100 μg L − 1 ) [6].…”
Section: Pyrethroid Residues In the Soilmentioning
confidence: 99%
“…Furthermore, the risk assessment of synthetic pyrethroids in the tropical soil of a tea plantation has never been performed due to the absence of pyrethroids detected in the soils. Numerous studies to determine and monitor pyrethroids in various plantation and farmland in tropical countries, including Malaysia [12], China [13], India [14], Pakistan [15], the Philippines [16], and Ghana [17] have been conducted. However, there is limited information regarding the presence of pyrethroids in the tropical soil of tea plantation such as in West Bengal, India [18].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the soils of hydrosystems constitute the compartment of the environment that is heavily contaminated by these agrochemicals, even though they constitute the interface of interactions with other compartments of the environment [10] [11] [12]. In addition, water resources and food products, especially those in developing countries in West Africa that do not have permanent quality monitoring, remain the environmental Journal of Agricultural Chemistry and Environment compartments most exposed to the increasing contamination of soils by nitrogen and pesticides [13]- [19]. On the other hand, the transfer of these agricultural pollutants to the water resources of a catchment area appears to be more important during flood periods, in both dissolved and particulate form, depending on several control factors [20] [21] [22].…”
Section: Introductionmentioning
confidence: 99%